2018
DOI: 10.1093/ofid/ofy303
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Echocardiography in Patients With Staphylococcus aureus Bacteremia at Low Risk of Endocarditis

Abstract: BackgroundThe risk of endocarditis among patients with Staphylococcus aureus bacteremia is not uniform, and a number of different scores have been developed to identify patients whose risk is less than 5%. The optimal echocardiography strategy for these patients is uncertain.MethodsWe used decision analysis and Monte Carlo simulation using input parameters taken from the existing literature. The model examined patients with S aureus bacteremia whose risk of endocarditis is less than 5%, generally those with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…group (P ϭ 0.03). This is consistent with recent evidence suggesting a limited benefit from echocardiography in LR-SAB (27)(28)(29). Much of the echocardiography done in both groups was not under the recommendation of the ID service, since we do not typically request it for patients with LR-SAB.…”
Section: Discussionsupporting
confidence: 91%
“…group (P ϭ 0.03). This is consistent with recent evidence suggesting a limited benefit from echocardiography in LR-SAB (27)(28)(29). Much of the echocardiography done in both groups was not under the recommendation of the ID service, since we do not typically request it for patients with LR-SAB.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, performing an echocardiogram was also a protective factor, albeit not statistically significantly in our study. In cases of SAB at low risk for infective endocarditis (IE), echocardiography is not associated with survival (Heriot et al, 2018); nonetheless, up to 22% of SAB have IE and differences in mortality are evident at 180 days when IE is present (Rasmussen et al, 2011). A systematic screening of SAB patients with echocardiography revealed that 25% of patients were diagnosed with IE although clinical suspicion was only present in 7% (Fowler et al, 1997); these findings suggest that echocardiography should be performed in all SAB patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] It may be difficult to statistically demonstrate the non-inferiority of outcomes depending on testing strategy in a population with a low prevalence of the disease. [ 34 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, it would be difficult to include enough patients at low risk of IE in the study to ensure sufficient statistical power. [ 34 ]…”
Section: Discussionmentioning
confidence: 99%